225k views
1 vote
13.......................

13.......................-example-1
User DadyByte
by
5.5k points

1 Answer

4 votes

Answer:

The answer is (d) ⇒
pq^(2)r\sqrt[3]{pr^(2)}

Explanation:

* To simplify the cube roots:

If its number then the number must be written in the form x³

then we divide the power by 3 to cancel the radical

If its variable we divide its power by 3 to cancel the radical


\sqrt[3]{p^(4)q^(6)r^(5)}=p^{(4)/(3)}q^{(6)/(3)}r^{(5)/(3)}}


p^{(4)/(3)}q^(2)}r^{(5)/(3)}=p^{1(1)/(3)}q^(2)r^{1(2)/(3)}


p^{(1)/(3)}=\sqrt[3]{p}


r^{(2)/(3)}=\sqrt[3]{r^(2)}


p(p)^{(1)/(3)}q^(2)r(r)^{(2)/(3)}=p(\sqrt[3]{p})q^(2)r(\sqrt[3]{r^(2)})


prq^(2)\sqrt[3]{pr^(2)}}

∴ The answer is (d)

User Jukebox
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.